Determination of estuarine sedimentation rates using 230Thexcess and 230Thexcess/232Th ratio methods in the Paka estuary, Malaysia - Yunus, Kamaruzzaman; Willison, KYS; Ong, Meng Chuan (Academic Journals Inc., USA, 2011)
The vertical profiles of 230Thexcess and 230Thexcess/232Th in a sediment core have been used to determine the sedimentation rates of Terengganu River estuary, Malaysia. Applying the 230Thexcess and 230Thexcess/232Th method, U and Th isotopic involved complete dissolution of the samples, followed by separation on anion exchange, average sedimentation rates of 1.02 and 1.01 cm year-1 were obtained, respectively. The results of the accretion rate obtained from the both methods are consistent with average sedimentation rates of 1.01 cm year-1. Assuming that the accretion rate values are accurate, this may imply that the sediments at the deepest core at 14 cm were deposited during the last 14.2 years ago.